Adaptation of Questionnaire Measuring Working Conditions and Health Problems Among Iranian Nursing Personnel - Narges Arsalani, RN, MSc; Masoud Fallahi-khoshknab, RN, PhD; Mostafa Ghaffari, MD, MPH, PhD; Malin Josephson, RN, PhD; Monica Lagerstrom, RN, PhD (Elsevier, 2011)
Purpose: To adapt a questionnaire in the Persian language measuring working conditions and health problems among nursing personnel. A further aim was to test the validity and reliability of the questionnaire. Methods: The adapted questionnaire was based on three well-established questionnaires. Physical working conditions items were from Nurse Early Exit Study. Psychosocial working conditions scales were included from Copenhagen Psychosocial Questionnaire which contains two scales on general and mental health as well. The Nordic Musculoskeletal Questionnaire was the origin of the musculoskeletal disorders questions. During the culture adaptation process, an expert panel method was used. To achieve equivalence between the sources and target version, some changes were made by the expert panel. Then the questionnaire was examined in the field for face validity and construct validity (n = 92) among Iranian nursing personnel from two hospitals. Construct validity was assessed using a priori hypothesized correlations of the outcomes with exposures. Finally the adaptation process was completed by reliability assessment using Cronbach's alpha and Intra-class Correlation Coefficient (ICC). Results: The construct validity result was the correlation of the health outcome with the work-related exposure (physical rs = .71 and psychosocial rs = .66). In the reliability assessment, Cronbach's alpha and ICC were .60 and .70 respectively. Conclusion: The findings show that the adapted questionnaire has an acceptable conceptual structure and provides reliable information from the nursing profession. Consequently, the questionnaire is applicable to work situation studies among nurses and other health care workers.